Energy levels of nuclei 40Sc and 40K as a function of semi-classical coupling angle θ1,2 within the modified surface delta-interaction - Dalal Naji Hameed; Ali Khalaf Hasan (Ядерна фізика та енергетика)
In this work, nuclear shell model was applied using modified surface delta-interaction to calculate, in particle-hole state, the energy levels of isobar nuclei 40Sc and 40K. Particles are in the model space (1f7/2) while the holes are found in the model space (1d3/2, 1s1/2, 1d5/2). The total angular momentum and parity are identified for possible particles and holes in nuclei above. Thus, we have used a theoretical study to find relationship between energy levels and the semi-classical coupling angle θ1,2 at different orbitals within particle-hole configuration. We notice the energy levels seem to follow two universal functions which depend on the semi-classical coupling angles θ1,2. We found the theoretical data agree to the experimental data.